Pedological Analysis of Viticulture Soils in Nashik District, Maharashtra - Incubator, Sairam (Journal of Research in Science and Engineering, 2025)
Fertility status of the soil is an important aspect in grape growing soils. It governs the Nutrients present in the soils and control the yields of crops. Nashik District is well known as a grape city was selected for the study. Fifteen representative villages were chosen and different number of surface soil samples (0-20cm) collected and analyzed for physico-chemical properties and available N, P, K, status. Results revealed that texture of the soils varied from clay loam to clay. Soil samples were found high in organic carbon. The soils were low to moderate in available nitrogen content, very low in available phosphorous content while, the available potassium indicates very high content. Significant positive correlations were found to exist between organic carbon and available N, P, K status of soil under study.